Implementasi Ekologi Hindu dalam Mendukung SDGs melalui Kegiatan Pelestarian Lingkungan - Srirahayu Puspawati; Anak Agung Istri Anom; Ida Kade Suparta; I Nengah Putra Kariana (IAHN Gde Pudja Mataram, 2026)
Implementation of sustainable ecology from a Hindu perspective through tree planting and beach clean-up activities was conducted by by the academic community of IAHN Gde Pudja Mataram, Lombok, Indonesia. This Community Service Program (PkM) was conducted as a collaborative action with local communities. The outcomes of the program were measured using a qualitative case study approach through participatory observation, unstructured interviews, and document analysis. The activities showed that tree planting supports vana kertiḥ (forest preservation), while beach clean-up efforts contribute to samudra kertiḥ (marine ecosystem conservation). Guided by the principles of ahiṁsā (non-violence) and niśkāma karma (selfless action), the program enhanced ecological awareness among participants. Aligned with SDG 13 (Climate Action) and SDG 14 (Life Below Water), this initiative demonstrates the effectiveness of integrating Hindu values into environmental management and offers a replicable model of religion-based community service for other educational institutions, despite ongoing challenges such as limited resources and low community involvement.